Global Scientific Trends On Nutrition Apps to Support Healthy Lifestyle in Digital Age - Muktiarni, Muktiarni; Rahayu, Nur Indri; Ismail, Affero (Universitas Komputer Indonesia, 2023)
Technological developments have brought about significant changes in the way people manage their health and fitness, especially through nutrition apps. Bibliometric analysis is used in the article to help discover current trends in the use of nutrition apps that support a healthy lifestyle. Key focuses of this trend include personalization, easy access to nutritional information, and integration with other health devices. In addition, this article also explores the positive impact of using nutrition apps on users' health awareness and behavior, as well as the challenges faced, such as data privacy issues and the need for scientific validation of the recommendations provided. The Scopus database was used to search for article data. Search results on the Scopus database found 107 documents. The development of publication of articles regarding nutritional applications to support a healthy lifestyle can be said to be quite increasing every year, although in 2023, 2019 and 2017 there has been a decline. There are a total of 175 countries that have contributed to publications regarding the use of nutrition applications to support a healthy lifestyle. Through this analysis, it is hoped that it can provide insight into the important role of nutritional applications in supporting a healthy lifestyle in the digital era